PEMBERDAYAAN PEREMPUAN (Transformasi menuju partisipasi politik) - Marniyati, Sabar (Universitas Surakarta, 2011)
The capacity of women in politics in Indonesia to date has not shown significant progress. This is evident from not fulfilling the quota of women serving in government and political institutions, thus triggering the apolitical attitude of women. Therefore, empowerment of women in politics into a critical discourse to encourage more women go into politics. Efforts must be made by government and non government agencies that have the empowerment of women equal to men.